Synthesis of Asymmetrical Organic Carbonates using CO2 as a Feedstock in AgCl/Ionic Liquid System at Ambient Conditions. Issue 6 (7th February 2017) - Hu, Jiayin; Ma, Jun; Lu, Lu; Qian, Qingli; Zhang, Zhaofu; Xie, Chao; Han, Buxing
Abstract: Synthesis of asymmetrical organic carbonates from the renewable and inexpensive CO2 is of great importance but also challenging, especially at ambient conditions. Herein, we found that some metal salt/ionic liquid catalyst systems were highly active for the synthesis of asymmetrical organic carbonates from CO2, propargylic alcohols, and primary alcohols. Especially, the AgCl/1‐butyl‐3‐methylimidazolium acetate ([Bmim][OAc]) system was very efficient for the reactions of a wide range of substrates at room temperature and atmospheric pressure, and the yields of the asymmetrical organic carbonates could approach 100 %. The catalyst system could be reused at least five times without changing its catalytic performance, and could be easily recovered and reused. A detailed study indicated that AgCl and [Bmim][OAc] catalyzed the reactions cooperatively, resulting in unique catalytic performance. Abstract : Asymmetry is all ! A series of asymmetrical organic carbonates can be synthesized efficiently by the reaction of CO2 with propargylic alcohols and primary alcohols under ambient conditions using AgCl/[Bmim][OAc] as catalyst and solvent, and the yields of the desired products can approach 100 %.